1979
DOI: 10.3171/jns.1979.50.1.0045
|View full text |Cite
|
Sign up to set email alerts
|

Spondylolisthesis after multiple bilateral laminectomies and facetectomies for lumbar spondylosis

Abstract: ✓ The authors report a further 3-year follow-up review of a series of 59 patients suffering with intractable pain due to lumbar spondylosis and treated by multiple-level bilateral laminectomies and facetectomies. Routine postoperative x-ray examination revealed that six of 59 patients had developed spondylolisthesis. Two of the six were symptomatic and required a secondary fusion procedure. Analysis of the patients who had developed vertebral slippage revealed that 6% of the patients with only two levels (L-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 1 publication
1
43
0
2
Order By: Relevance
“…Numerous studies have implicated degenerative spondylolisthesis as a poor prognostic indicator. [9,26,30,36,42,50,61,65,68,69,73] Several authors have reported less favorable outcomes in women, [9,19,27,34,50,65,68,69] younger patients, [32,64,67,73] and patients undergoing repeated lumbar surgery. [15,28,52,61,72] Patient characteristics that warrant the consideration of arthrodesis (PLIF) in addition to decompression are listed in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have implicated degenerative spondylolisthesis as a poor prognostic indicator. [9,26,30,36,42,50,61,65,68,69,73] Several authors have reported less favorable outcomes in women, [9,19,27,34,50,65,68,69] younger patients, [32,64,67,73] and patients undergoing repeated lumbar surgery. [15,28,52,61,72] Patient characteristics that warrant the consideration of arthrodesis (PLIF) in addition to decompression are listed in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Tile, et al, [67] reported that all of their patients with spondylolisthesis developed progressive slippage postoperatively. Shenkin and Hash [64] followed 59 patients after multiple-level bilateral laminectomies and facetectomies and reported that 15% of patients in whom three or more levels were removed developed progressive spondylolisthesis. Robertson, et al, [58] reported that 58% of 33 patients treated by means of decompressive laminectomy showed postoperative spondylolisthesis of greater than 5% within 1 year of surgery.…”
Section: Pathological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laminectomy including removal of spinous process, supraspinous ligament, interspinous ligament, lamina and ligamentum flavum jeopardize the integrity of posterior complex of the spine. However, iatrogenic instability following extensive laminectomy occurs in some patients with degenerative lumbar canal stenosis or in patients who are associated with pre-existing spondylolisthesis 69. Long segment fusions have been done by some workers to obviate postoperative instability; however, such operations result in loss of motion of lumbar spine and predisposes the spine for adjacent level degeneration 10–13.…”
Section: Introductionmentioning
confidence: 99%
“…8,18,20,44,53,61 DLSS is currently the most common indication for spinal surgery in patients older than 65 years, 13,19,20,53,56 and several studies have shown better surgical results over more conservative therapies. 2,5,6,10,25,27,38,63 However, open conventional laminectomy has been criticized because of its limited success rate 60 and potential for negative side effects, such as the increased risk of postoperative instability and the subsequent need for secondary fusion surgery; this is again associated with additional risks and costs, 15,23,28,35,36,52 and also persistent postoperative back pain due to prolonged muscle retraction. 1,39,54 As a result of these potential side effects, the development of less invasive techniques was initiated.…”
mentioning
confidence: 99%